Investigation of the polyphenol composition of red oak (Quercus rubra L.) raw materials - Konovalova Olena; Omelkovets Tetiana; Sydora Natalia; Hurtovenko Iryna; Kalista Mariaa; Shcherbakova Olha (Technology Center, 2026)
The aim of the work was to determine the main groups of polyphenolic compounds in Quercus rubra L. raw materials.
Materials and methods. The leaves and annual shoots of Northern Red Oak used for research were collected in August in Lisnyky village of Obuhiv district of Kyiv Oblast (Ukraine). Determination of the component composition and quantitative content of flavonoids (including separately catechins), hydroxycinnamic acids, and phenolic acids were carried out in the samples of air-shade-dried crushed raw material to a particle size of 3 mm by the method of high-performance liquid chromatography (HPLC). Agilent Technologies 1200 liquid chromatograph was used for liquid chromatography.
Results. Using the HPLC method, 18 polyphenolic compounds were identified in leaves and annual shoots of Northern Red Oak, in particular, flavonoids: rutin, quercetin-3-β-glucoside, luteolin, neohesperidin; catechins: catechin, epicatechin, epicatechin gallate, gallocatechin; hydroxycinnamic acids: chlorogenic, caffeic, trans-ferulic, trans-cinnamic, p-coumaric, hydroxyphenylacetic, benzoic, syringic, sinapic acids; phenolic acid is gallic acid. The dominant component among flavonoids is rutin (323.43 mg/100 g) (in the composition of catechins, epicatechin gallate (25.45 mg/100 g) prevails); among hydroxycinnamic acids in Northern Red Oak raw materials, chlorogenic acid (139.62 mg/100 g) and sinapic acid (74.64 mg/100 g) prevail.
Conclusions. The obtained results point to the prospects of further phytochemical and pharmacological studies of Quercus rubra raw materials, with the aim of creating new plant substances based on it with antioxidant, anti-inflammatory, and antiviral activity. © The Author(s) 2023.
Author keywords
catechins; flavonoids; high-performance liquid chromatography (HPLC); hydroxycinnamic acids; leaves; Northern Red Oak; Quercus rubra; shoots